Drivers of Retail Supply Chain Efficiency: Moderating Effect of Lean Strategy - Rana Sohel S. M.; Abdullah Osman; Arman Hadi Abdul Manaf; Mohd Suberi Abdul Halim; Mohammad Solaiman (International Journal of Supply Chain Management, 2016)
The retail chain store business is an infant stage of growth and development in Bangladesh and so are the supply chain management practices in this sector. The main objective of this study is to identify the key drivers of retail supply chain efficiency. Moreover this study aims at examining the moderating effect of lean supply chain strategy on the link between supply chain drivers and performance. For the purpose of the study, data were collected with a structured questionnaire from 115 participants consisting of outlet and supply chain managers of some selected retail chain stores in Bangladesh. Collected data were analyzed using partial least squares (PLS) structural equation modeling with the support of the software Smart PLS 2.0 M3. Findings revealed that out of five supply chain drivers, four namely inventory management, use of IT, transportation management and coordination were the most significant determinants of retail supply chain efficiency while suppliers role was found to be negatively correlated. Moderating effect of lean strategy was also noticed on the link between two drivers namely transportation management and coordination with retail supply chain efficiency.